Diversifikasi Pendapatan Terhadap Kerentanan Kemiskinan pada Rumah Tangga Petani Padi Sawah di Kecamatan Kabila Kabupaten Bone Bolango - Abdul Sofyan Polimango; Mahludin H. Baruwadi; Fitri Hadi Yulia Akib (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the effect of income diversification on poverty vulnerability in rice farming households in Kabila District, Bone Bolango Regency, Gorontalo Province. Income diversification is viewed as a crucial strategy to improve the economic resilience of farming households, which are heavily dependent on the agricultural sector. The research uses a quantitative approach, analyzing data from 74 respondents selected through sampling techniques. Data was collected using a questionnaire that covered various income sources, income inequality, and the level of vulnerability to poverty. The results show that the income structure of households is dominated by income from rice farming (45%), while small businesses (25%) and formal and informal employment (15%) also contribute significantly. The Gini coefficient analysis of income inequality indicates a moderate level of inequality with a value of 0.42, with the non-agricultural sector showing higher inequality (0.45) compared to agriculture (0.38). Income diversification has a significant negative relationship with poverty vulnerability, with a correlation coefficient of −0.60. The regression model indicates that 42% of the variation in poverty vulnerability is explained by income diversification, suggesting that households with more diverse income sources are less vulnerable to poverty. The study concludes that income diversification is an effective strategy in reducing the economic vulnerability of rice farming households. The findings underline the need for policies that support farmers' access to economic opportunities outside agriculture, such as skill training and access to business capital. These results provide a basis for local governments and stakeholders to formulate effective policies aimed at reducing poverty in rural areas.